Consumer Perceptions Of The Kasuari Brand White Cooden Oil Products (Case Study At The Nikmat Software Shop, Ambon City) - Firsandi Tomia; S. FW Thenu; MTF Tuhumury (International Journal of Education, Vocational and Social Science, 2025)
What are consumers' perceptions of the service and quality of cassowary brand eucalyptus oil products in the delicious souvenir shop in Ambon City. To determine the perception of service quality and the quality of cassowary brand eucalyptus oil products in the delicious souvenir shop in Ambon City, a survey method was used based on the consideration that this method is quite economical, quickly guarantees freedom and guarantees the confidentiality of respondents' identities so that it is easier to provide information or answers to perceptions. The quality of service includes physical evidence, responsiveness, assurance and empathy which has very good value. Likewise, consumers' perceptions of product quality include special characteristics, performance and durability which also have very good value. Service quality: physical evidence, brightness, responsiveness, assurance and empathy are classified as very good. In terms of indicators of consumer attention and needs, trust, safety and comfort, responsiveness and comfort. Product quality: special characteristics, performance and durability are classified in the very good category, in terms of appearance, quality, quality, aroma and durability.